Using value of statistical life approach for employee's compensation - Kaur, Rattanmeek (Artha Vijnana)
The method adopted under the Employee Compensation Act, 1923 for paying compensation in case of death of an employee suffers from anomalies which go to the very root of the legislation. It uses (3z(Bloss of dependents(3y (Bapproach and only pays economic damages, ignoring hedonic damages. Therefore, the amount arrived at is inadequate, failing to achieve the objective of welfare legislation and does not generate optimum level of deterrence. Adverse consequences of which are unaccounted externalities and increase in the number of fatal accidents due to suboptimal level of precaution. This paper makes a case study of the construction sector in India to understand these two problems. The alternative which can be adopted is Value of a Statistical Approach which originates from hedonic approach. It measures the value of life in terms of utility derived from life. This method will internalise the social cost and produce an optimum level of deterrence. The paper suggests a framework using VSL approach which can be applied by the courts while paying damages.- Reproduced s